Research Supports are Effective in Increasing Confidence with Research Skills in Early Career Academic Librarians - Koos, Jessica A. (Evidence Based Library and Information Practice, 2020)
A Review of: Ackerman, E., Hunter, J. & Wilkinson, Z. T. (2018). The availability and effectiveness of research supports for early career academic librarians. The Journal of Academic Librarianship, 44(5), 553-568. https://doi.org/10.1016/j.acalib.2018.06.001 Abstract Objective – To identify the type and efficacy of research supports currently available to early career academic librarians. Design – Survey. Setting – The United States. Subjects – 213 academic librarians who were not yet promoted or have received tenure, or those up to three years post-tenure or promotion. Methods – The researchers created a survey containing 39 closed and open-ended questions using the software Qualtrics. The question types included multiple choice, Likert scale, and free text. The survey was distributed through direct emails and various professional electronic mailing lists. Main Results – The majority of respondents listed finding time as the most significant barrier to conducting research. Respondents listed informal mentoring as the most commonly used and most widely available form of research support. Statistical analyses revealed that for every type of research support a librarian engaged in, on average confidence increased by 0.10. Conclusion – Engagement in formal and informal research supports may influence early career academic librarians’ confidence levels in regards to conducting research projects. Academic institutions as well as professional organizations should ensure that ample opportunities are available.